Mapping QTL for fusarium head blight resistance in Chinese wheat landraces - Cai, Jin (Kansas State University, 2012)
Fusarium head blight (FHB) is one of the most devastative diseases in wheat. Growing resistant cultivars is one of the most effective strategies to minimize the disease damage. Huangcandou (HCD) is a Chinese wheat landrace showing a high level of resistance to FHB spread within a spike (type II). To identify quantitative traits loci (QTL) for resistance in HCD, a population of 190 recombinant inbred lines (RILs) were developed from a cross between HCD and Jagger, a susceptible hard winter wheat (HWW) released in Kansas. The population was evaluated for type II resistance at the greenhouses of Kansas State University. After initial marker screening, 261 polymorphic simple-sequence repeats (SSR) between parents were used for analysis of the RIL population. Among three QTL identified, two from HCD were mapped on the short arms of chromosomes 3B (3BS) and 3A (3AS). The QTL on the distal end of 3BS showed a major effect on type II resistance in all three experiments. This QTL coincides with a previously reported Fhb1, and explained 28.3% of phenotypic variation. The QTL on 3AS explained 9.7% of phenotypic variation for mean PSS over three experiments. The third QTL from chromosome 2D of Jagger explained 6.5% of phenotypic variation. Allelic substitution using the closest marker to each QTL revealed that substitution of Jagger alleles of two QTL on 3AS and 3BS with those from HCD significantly reduced the PSS. HCD containing both QTL on 3AS and 3BS with a large effect on type II resistance can be an alternative source of FHB resistance for improving FHB type II resistance in wheat. Besides, meta-analyses were used to estimate 95% confidence intervals (CIs) of 24 mapped QTL in five previously mapped populations derived from Chinese landraces: Wangshuibai (WSB), Haiyanzhong (HYZ), Huangfangzhu (HFZ), Baishanyuehuang (BSYH) and Huangcandou (HCD). Nineteen QTL for FHB type II resistance were projected to 10 QTL clusters. Five QTL on chromosomes 1A, 5A, 7A, and 3BS (2) were identified as confirmed QTL that have stable and consistent effects on FHB resistance and markers in these meta-QTL regions should be useful for marker-assisted breeding.
Keywords: FHB; QTL mapping; Meta-analysis; Chinese landraces; Agronomy (0285)